2020
DOI: 10.1111/codi.15463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on bowel function restoration following ileostomy closure in rectal cancer patients: a randomized controlled trial

Abstract: Aim:The aim was to determine the efficacy of probiotics in restoring bowel function following ileostomy reversal in patients with rectal cancer.Method: This was a pilot, randomized, double-blind, placebo-controlled trial. The probiotic used in this study, Lactobacillus plantarum CJLP243, was derived from kimchi.Patients were randomly allocated to a probiotic or placebo group and medication was taken once daily from preoperative day 1 to day 21. Primary outcomes were the Memorial Sloan Kettering Cancer Centre B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 43 publications
1
44
0
1
Order By: Relevance
“…This correlation disappears between the third and sixth month, when diversion colitis becomes non-existent both endoscopically and microscopically. This fact coincides with the transitory and limited modulatory effect that probiotics produces on the intestinal mucosa (43)(44)(45)(46)(47) and with the recovery curve of intestinal function published in other studies (7,9). However, as the main limitation of our study has been the sample size we cannot make definitive statements about the effectiveness of this technique.…”
Section: Discussionsupporting
confidence: 80%
“…This correlation disappears between the third and sixth month, when diversion colitis becomes non-existent both endoscopically and microscopically. This fact coincides with the transitory and limited modulatory effect that probiotics produces on the intestinal mucosa (43)(44)(45)(46)(47) and with the recovery curve of intestinal function published in other studies (7,9). However, as the main limitation of our study has been the sample size we cannot make definitive statements about the effectiveness of this technique.…”
Section: Discussionsupporting
confidence: 80%
“…We decided to carry out our study to compare results after stimulation of the efferent loop with probiotics in patients previously operated on for colorectal carcinoma. Based on systematic reviews about the use of probiotics as treatment of other gastrointestinal pathologies [ 18 , 19 , 20 ], we considered that this stimulation would achieve the repopulation of the excluded colon, activating the cellular absorption mechanisms, increasing motility, and decreasing efferent loop atrophy, so that after closure ileostomy, the return to normality would be faster, with a shorter time required to re-establish oral transit and tolerance, reducing the onset of postoperative ileus and the duration of hospital stay. We chose the formulation of probiotics with the highest number of strains, which had an adequate synergistic and complementary effect between them, and the highest concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies involved interventions examining the effects of probiotics, [38][39][40][41]44,46,48 3 investigated prebiotics, 42,43,45 and 2 studies used a combination of prebiotics and probiotics, referred to as a synbiotic. 37,47 As seen in Table 1, treatment duration varied from 2 to 24 weeks.…”
Section: Prebiotic and Probiotic Intervention Characteristicsmentioning
confidence: 99%
“…As seen in Table 1, among interventions using probiotics [38][39][40][41]44,46,48 or synbiotics, 37,47 various probiotic strains and doses were used. The most consistently used probiotic strains belonged to the Lactobacillus genus (100%), [37][38][39][40][41]44,[46][47][48] followed by those from the Bifidobacterium genus (56%). 37,38,40,44,46 Doses and treatment duration varied from one study to the next, with minimal consistency observed between studies.…”
Section: Prebiotic and Probiotic Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation